2011
DOI: 10.1371/journal.pone.0020500
|View full text |Cite
|
Sign up to set email alerts
|

Gβγ and the C Terminus of SNAP-25 Are Necessary for Long-Term Depression of Transmitter Release

Abstract: BackgroundShort-term presynaptic inhibition mediated by G protein-coupled receptors involves a direct interaction between G proteins and the vesicle release machinery. Recent studies implicate the C terminus of the vesicle-associated protein SNAP-25 as a molecular binding target of Gβγ that transiently reduces vesicular release. However, it is not known whether SNAP-25 is a target for molecular modifications expressing long-term changes in transmitter release probability.Methodology/Principal FindingsThis stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 64 publications
4
51
0
Order By: Relevance
“…In addition to binding to SNAP-25, Yoon et al (2007) showed that G␤␥ also binds individually to the other SNARE proteins, syntaxin 1A and synaptobrevin, as well as to the t-SNARE dimer (SNAP-25 with syntaxin 1A) and to the ternary SNARE complex. This mechanism of G␤␥-mediated inhibition of secretion has been identified in neurons (Blackmer et al, 2001;Delaney et al, 2007;Zhang et al, 2011), chromaffin cells (Yoon et al, 2008), and pancreatic ␤-cells (Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In addition to binding to SNAP-25, Yoon et al (2007) showed that G␤␥ also binds individually to the other SNARE proteins, syntaxin 1A and synaptobrevin, as well as to the t-SNARE dimer (SNAP-25 with syntaxin 1A) and to the ternary SNARE complex. This mechanism of G␤␥-mediated inhibition of secretion has been identified in neurons (Blackmer et al, 2001;Delaney et al, 2007;Zhang et al, 2011), chromaffin cells (Yoon et al, 2008), and pancreatic ␤-cells (Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 92%
“…In the presynapse, G␤␥ has been shown to be an important regulator of neurotransmission through interactions with calcium channels (Hille, 1994;Ikeda and Dunlap, 1999;Dolphin, 2003) and with the secretory machinery itself (Blackmer et al, 2001Gerachshenko et al, 2005; for review, see Betke et al, 2012). In particular, G␤␥ binds directly to the ternary SNARE complex (a trimer of SNAP-25, syntaxin 1A, and synaptobrevin), as established in biochemical as well as in vitro assays (Blackmer et al, 2001Gerachshenko et al, 2005;Photowala et al, 2006;Delaney et al, 2007;Yoon et al, 2007Yoon et al, , 2008Zhao et al, 2010;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of exocytosis at this synapse was shown to be mediated by the a 2 adrenergic receptor via the Gbg-SNARE interaction (Delaney et al, 2007). Other mammalian studies include that by Zhang et al, (2011), where introduction of Gbg-scavenging peptides into CA3 hippocampal terminals blocked group II metabotropic glutamate receptor-mediated presynaptic depression of release, and introduction of BoNT/A into Schaffer collateral CA1 synapses reduced induction of long-term depression. These studies are both heavily reliant upon the introduction of Gbg-scavenging peptides and lightchain botulinum toxins to demonstrate the involvement of the Gbg-SNARE interaction.…”
Section: Snap25 C-terminal Mutants Resistant To Gbg Inhibitionmentioning
confidence: 99%
“…Presynaptic G i/o -coupled GPCRs have been shown to be relevant drug targets for anxiety and schizophrenia (Swanson et al, 2005;Patil et al, 2007), but the mechanisms for these effects are not known. The Gbg-SNARE interaction has been shown to be functionally relevant for a number of presynaptic G i/o -coupled GPCRs (Glitsch, 2006;Delaney et al, 2007;Heinke et al, 2011;Zhang et al, 2011;Betke et al, 2012). To explore these and other potential areas of therapeutic relevance further, a transgenic model deficient in the Gbg-SNARE interaction is required.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that proteolysis of SNARE proteins alters facilitation and depression in a specific way [48,50]. By this, changes in neurotransmission by BTX may be able to influence clinical phenotypes like depression, sleep and pain.…”
Section: Discussionmentioning
confidence: 99%